Computer use and the wage structure in Austria - Helmut Hofer; Monika Riedel (Institute for Advanced Studies (IHS), 2003)
In this paper we examine the relationship between computer premium and job position in Austria. We estimate cross-section wage equations and control for selectivity of computer use via a treatment effects model. We find that the size of the wage effect attributed to computer use varies significantly between job hierarchies. Persons in higher positions receive relatively lower rewards for computer use than workers at lower hierarchy levels. Overall we find that computerisation increased wage inequality in Austria. However, hierarchy-related differences in the relative computer premium in Austria might moderate the effects of computer use on the wage distribution.
Keywords: C21; J30; O33; 330; technological change; computer wage premium; wage inequality; Computer; Mediennutzung; Erwerbstätigkeit; Bildungsniveau; Lohnstruktur; Österreich